A A Mobile Game : Sarawak Heritage - Gelayan, Raphael; Mohd Supian, Jessifa Joanna (Journal of Computing Technologies and Creative Content, 2021)
The cultural heritage of Sarawak appears to still have a limited level of awareness among men, as well as Malaysians themselves, particularly those in western Malaysia. Only several people recognize Sarawak's uniqueness and also what makes it different from other countries around the globe. There are more than 27 diverse ethnic groups in Sarawak, totaling over 2.6 million people. The project aims to develop a mobile game featuring Sarawak's cultural heritage, which includes traditional clothes, cuisine, plants and animals, musical equipment, and weapons. It is assumed that this game would contribute to expanding recognition and attention to how astounding Sarawak and its heritage are. The smartphone game is being used in an educational way and seeks to encourage learning through fun, visualization, classical music, and knowledge provided by this platform. This alone would make learning more effective and convenient. On the other hand, this analysis will be carried out utilizing the quantitative approach, in which surveys and questionnaires would be circulated both on paper and online. In the conclusion, this project has become a great success and has fulfilled the goals and objectives set since the initiation of the project.